Detecting false intent using eye blink measures - Marchak, Frank M. (Frontiers in Psychology, 2013)
Eye blink measures have been shown to be diagnostic in detecting deception regarding past acts. Here we examined – across two experiments with increasing degrees of ecological validity – whether changes in eye blinking can be used to determine false intent regarding future actions. In both experiments, half of the participants engaged in a mock crime and then transported an explosive device with the intent of delivering it to a ‘contact’ that would use it to cause a disturbance. Eye blinking was measured for all participants when presented with three types of questions: relevant to intent to transport an explosive device, relevant to intent to engage in an unrelated illegal act, and neutral questions. Experiment 1 involved standing participants watching a video interviewer with audio presented ambiently. Experiment 2 involved standing participants questioned by a live interviewer. Across both experiments, changes in blink count during and immediately following individual questions, total number of blinks, and maximum blink time length differentiated those with false intent from truthful intent participants. In response to questions relevant to intent to deliver an explosive device versus questions relevant to intent to deliver illegal drugs, those with false intent showed a suppression of blinking during the questions when compared to the ten second period after the end of the questions, a lower number of blinks, and shorter maximum blink duration. The results are discussed in relation to detecting deception about past activities as well as to the similarities and differences to detecting false intent as described by prospective memory and arousal.